Fruits of the forest: human stable isotope ecology and rainforest adaptations in Late Pleistocene and Holocene Sri Lanka - Roberts, P (2016)
Despite ecological, anthropological, and archaeological debate surrounding their desirability as habitats for human occupation, tropical rainforests have received relatively little attention in discussions of Homo sapiens' Pleistocene dispersal. Sri Lanka has yielded some of the earliest dated fossil and material culture evidence (c. 38-35,000 cal. years BP) for our species in a modern rainforest context beyond Africa. Nevertheless, assertions in Sri Lanka, and elsewhere, regarding early human rainforest reliance have been largely based on coarse or 'off-site' palaeoenvironmental records, and the overall role of these environments in human subsistence strategies has remained uncertain. This study applies stable carbon and oxygen isotope analysis to Sri Lankan human fossil, and associated faunal, tooth enamel dated to between 36-29,000 and 3,000 cal. years BP, in order to directly test human rainforest resource reliance, reconstruct a stable isotope ecology, and develop 'on-site' palaeoenvironmental records for Late Pleistocene-Holocene Sri Lankan rainforest foragers. Stable carbon and oxygen isotope analysis of modern Sri Lankan primates, and stable carbon, oxygen, and nitrogen isotope analysis of modern plant samples from the Polonnaruwa Nature Sanctuary, are also performed to investigate the ecology of Sri Lankan primates on which Late Pleistocene-Holocene forager subsistence strategies were focused. The results demonstrate that Homo sapiens relied on rainforest resources in Sri Lanka from c. 36-29,000 cal. years BP until the Iron Age c. 3 cal. years BP, even when open environments, and their corresponding resources, were available. This remains the case through periods of evident environmental change at the Last Glacial Maximum and even upon the arrival of agriculture in the island's tropical forests. The primate stable isotope data prove difficult to interpret as ecological niche separation in the absence of observation data. Nonetheless, humans were evidently able to not only use but also rapidly specialise in the exploitation of South Asia's rainforests.